Optic toxicity in radiation treatment of meningioma: a retrospective study in 213 patients - Farzin, Mostafa; Molls, Michael; Kampfer, Severin; Astner, Sabrina; Schneider, Ralf; Roth, Karin; Dobrei, Michaela; Combs, Stephanie; Straube, Christoph (Journal of Neuro-Oncology, 2016)
In this retrospective evaluation, we correlated radiation dose parameters with occurrence of optical radiation-induced toxicities. 213 meningioma patients received radiation between 2000 and 2013. Radiation dose and clinical data were extracted from planning systems and patients’ files. The range of follow-up period was 2–159 months (median 75 months). Median age of patients was 60 years (range 23–86). There were 163 female and 50 male patients. In 140 cases, at least one of the neuro-optic structures (optic nerves and chiasm) was inside the irradiated target volumes. We found 15 dry eye (7 %) and 24 cataract (11.2 %) cases. Median dose to affected lachrymal glands was 1.47 Gy and median dose to affected lenses was 1.05 Gy. Age and blood cholesterol level in patients with cataract were significantly higher. Patients with dry eye were significantly older. Only two patients with visual problems attributable to radiation treatment were seen. They did not have any risk factors. Maximum and median delivered doses to neuro-optic structures were not higher than 57.30 and 54.60 Gy respectively. Low percentages of cases with radiation induced high grade optic toxicities show that modern treatment techniques and doses are safe. In very few patients with optic side effects, doses to organs at risk were higher than the defined constraint doses. This observation leads to the problem of additional risk factors coming into play. The role of risk factors and safety of higher radiation doses in high grade meningiomas should be investigated in more comprehensive studies.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cataract; Dry eye; Meningioma; Optic neuropathy; Radiation treatment